Research on the Complexity Mechanism of Decoy Strategies Based on Multiagent Simulation - Zhen Li; Xiaoyu Bao; Qingfeng Meng; Pengqun Shen (Complexity)
Competition and diffusion of products are of great significance to companies. In this study, various true decoy strategies are constructed using different combinations of price and quality. This paper then analyzes the performance of strategies using different product competition and diffusion scenarios. The influences of neighbor nodes, reconnection probability, and herd mentality on decoy effects are explored. The results show that setting an appropriate true decoy can enhance the competitiveness of a target product to some extent. Conversely, an inappropriate decoy strategy will play a negative role, encroaching on market share. In terms of effects, changes in neighbor nodes, reconnection probability, and herd mentality will not influence the direction of the evolution of a product for the same true decoy strategies. However, the speed of evolution will be affected. These findings provide a theoretical basis for enterprises taking action to enhance product competitiveness in the market.